Integrating Family Medicine and Pharmacology: A Holistic Approach to Modern Medical Science – An Expert Opinion - SK Sabir Rahaman (Journal of Integrated Health Sciences, 2025)
The convergence of family medicine and clinical pharmacology signifies a vital evolution in modern healthcare, particularly in the era of chronic diseases, polypharmacy, and rising healthcare expenditures. As healthcare systems globally pivot toward person-centered and community-oriented primary care, embedding pharmacological expertise into family medicine promises enhanced quality, safety, and cost-efficiency. This expert opinion article explores the rationale, benefits, and strategic implementation of integrating pharmacology into family medicine, contextualized within India’s healthcare evolution and international developments. The synthesis of holistic clinical care with pharmacological precision offers an innovative, scalable, and sustainable model to address the complex healthcare challenges of the 21st century.